Herstories on screen : feminist subversions of frontier myths - Cummins, Kathleen (Wallflower Press, 2020)
"From the late 1970s into the early 1990s, a generation of female filmmakers took aim at their home countries' popular myths of the frontier. Deeply influenced by second-wave feminism and supported by hard-won new access to governmental and institutional funding and training, their trailblazing films challenged traditionally male genres like the Western. Instead of reinforcing the myths of nationhood often portrayed in such films-invariably featuring a lone white male hero pitted against the "savage" and "uncivilized" native terrain-these filmmakers constructed counternarratives centering on women and marginalized communities. In place of rugged cowboys violently removing indigenous peoples to make the frontier safe for their virtuous wives and daughters, these filmmakers told the stories of colonial and postcolonial societies from a female and/or subaltern point of view. Herstories on Screen is a transnational study of feature narrative films from Australia, Canada, the United States, and New Zealand/Aotearoa that deconstruct settler-colonial myths. Kathleen Cummins offers in-depth readings of ten works by a diverse range of women filmmakers including Jane Campion, Julie Dash, Merata Mita, Tracey Moffat, and Anne Wheeler. She reveals how they skillfully deploy genre tropes and popular storytelling conventions in order to critique master narratives of feminine domesticity and purity and depict women and subaltern people performing acts of agency and resistance. Cummins details the ways in which second-wave feminist theory and aesthetics informed these filmmakers' efforts to debunk idealized Anglo-Saxon femininity and motherhood and lay bare gendered and sexual violence and colonial oppression"-- Provided by publisher
Keywords: Feminist films -- History and criticism.; Feminism and motion pictures.; Women in motion pictures.; Frontier and pioneer life -- In motion pictures.; Motion pictures and women.; Women in the motion picture industry.; Women motion picture producers and directors.; Films féministes -- Histoire et critique.; Féminisme et cinéma.; Femmes au cinéma.; Cinéma et femmes.; Femmes dans l'industrie cinématographique.; Productrices et réalisatrices de cinéma.; filmmakers.; PERFORMING ARTS -- Film -- History & Criticism.; Feminism and motion pictures; Feminist films; Motion pictures and women; Women in motion pictures; Women in the motion picture industry; Women motion picture producers and directors; Motion picture reviews; Criticism, interpretation, etc.; Motion picture reviews.; Comptes rendus de films.